Ultrahigh-solid high-temperature and high-pressure resistant phenolic epoxy heavy anti-corrosion coating and production process thereof

By adding specific ingredients to the epoxy phenolic anticorrosion coating, ultra-high solid high-temperature and high-pressure phenolic epoxy heavy anticorrosion coating is formed, which solves the problem of insufficient acid resistance and heat resistance of existing coatings in high-temperature and high-pressure environments, and achieves efficient and environmentally friendly corrosion resistance.

CN119505649APending Publication Date: 2025-02-25NORTHWEST YONGXIN PAINT COATINGS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411254295.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing epoxy phenolic anticorrosion coatings are insufficient in high temperature and high pressure environments, and have high VOC content and low solid content, which makes them difficult to increase thickness in construction, which poses safety hazards and environmental pollution problems.

Method used

Ultra-high solid high-temperature and high-pressure phenolic epoxy heavy anticorrosion coatings mixed with components one and two at a mass ratio of 6.5:1-8:1 are used. By adding ion exchange corrosion inhibitors, oxidized ceramic powders, high-quality thin-layer graphene dispersed slurries and other components, the acid resistance, heat resistance and corrosion resistance of the coating are improved.

Benefits of technology

The coating is achieved with excellent acid resistance, heat resistance and corrosion resistance, reducing VOC content, improving solid content and construction efficiency, and ensuring the safety and environmental protection of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses an ultrahigh-solid high-temperature-resistant and high-pressure-resistant phenolic epoxy heavy anti-corrosion coating and a production process thereof, and relates to the technical field of coatings. The coating is prepared by mixing a component I and a component II according to the mass ratio of (6.5: 1)-(8: 1), the component I is prepared from the following raw materials: novolac epoxy resin, epoxy resin, a dispersing agent, organic bentonite, an ion exchange corrosion inhibitor, silica powder, oxidized ceramic powder, high-quality thin-layer graphene dispersed slurry, carbon black, a defoaming agent, xylene, butanol and acetone; the raw materials of the component II are a modified alicyclic amine curing agent and a modified aliphatic amine curing agent. The coating has excellent acid resistance, heat resistance, long-acting corrosion resistance, wear resistance and high-temperature and high-pressure resistance, is a high-solid-content environment-friendly product, is low in VOC content, is suitable for an oil extraction pipeline application scene, is sprayed on the inner wall of a pipeline, and a coating layer and the surface of a metal pipeline are firmly adhered together, so that a chemical reaction between metal and external substances is effectively prevented, and the service life of the metal pipeline is prolonged. The service life of the pipeline can be prolonged, and cost is saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, and in particular to an ultra-high solid, high temperature and high pressure resistant phenolic epoxy heavy-duty anti-corrosion coating and a production process thereof. Background Art

[0002] Oil casing is the lifeline for oil well operation. It is a steel pipe used to support the wall of oil and gas wells to ensure the normal operation of the entire oil well during the drilling process and after completion. Each well uses several layers of casing according to different drilling depths and geological conditions. After the casing is lowered into the well, cement is used for cementing. Unlike oil pipes and drill pipes, it cannot be reused and is a one-time consumable material, accounting for more than 70% of all oil well pipes.

[0003] Due to different geological conditions and complex stress conditions downhole, higher requirements are placed on the quality of the casing itself. Once the casing itself is damaged for some reason, it may lead to reduced production of the entire well or even scrapped; in particular, the anti-corrosion coating of the casing is very critical, seriously affecting the operating efficiency and service life of the oil well. If the quality of the anti-corrosion coating does not meet the standards, it will cause pipeline corrosion, blockage and other problems, leading to reduced production and even closure of the gas well, causing huge economic losses.

[0004] The oil casing seals the oil and gas layer and the exposed part above. Crude oil contains a large amount of corrosive media such as sulfur, chloride ions, dissolved oxygen, etc. The casing is the deepest in the well. The underground oil and gas layer has a high pressure and high temperature, forming an extremely harsh corrosive environment. In the environment of corrosive media such as strong acids, alkalis and salts, high temperature and high pressure, the corrosion rate increases exponentially. In addition, the oil casing is subject to mechanical damage under stresses such as collision, pulling, pressing, bending and twisting during operation. It is difficult for the protective coating on the inner wall of the casing to meet these comprehensive performance indicators at the same time, especially the acid and alkali resistance under high temperature and high pressure environment is difficult to meet the standard requirements.

[0005] At present, the industry mostly uses epoxy phenolic anti-corrosion coatings for the inner wall protective coating of casing. Epoxy phenolic anti-corrosion coatings use different curing agents and fillers, and the product performance varies greatly, but basically all have the problem of poor acid resistance. Phenolic epoxy resin has high functionality, generally 2.3-3.6, and the paint film formed has high hardness, but is brittle, has poor wear resistance, low elongation, and is easy to peel off; while petroleum casing is subject to impact, collision, and mechanical damage under various applications during use, and high flexibility and adhesion are required. It is difficult for general plasticizers to solve the shortcomings of phenolic epoxy resin, and it will soften under high temperature and high pressure environment. The high temperature and high pressure resistance performance does not meet the standard requirements, and there are safety hazards.

[0006] In addition, the current epoxy phenolic anti-corrosion coating has a high VOC content, great environmental pollution, low solid content, and is difficult to increase the thickness during construction. Petroleum casing coating generally uses automated spraying equipment, and the construction environment temperature is -20 to 40°C, and it is dried and dried. When construction is carried out in a low temperature environment of -20°C, the space inside the casing and the oven is small, the ventilation is poor, and the solvent is difficult to evaporate, resulting in slow drying of the paint film, an uneven surface, and the appearance of black circles, sagging and other drawbacks, which seriously affect the coating quality and production efficiency.

[0007] Therefore, there are many problems with the existing epoxy phenolic anti-corrosion coatings used for petroleum casing, which is difficult to satisfy the industry. Summary of the invention

[0008] The object of the present invention is to provide an ultra-high solid high temperature and high pressure resistant phenolic epoxy heavy anti-corrosion coating and a production process thereof, so as to solve the problems raised in the above background technology.

[0009] On the one hand, the present invention provides an ultra-high solid high temperature and high pressure resistant phenolic epoxy heavy anti-corrosion coating, which is prepared by mixing component one and component two in a mass ratio of 6.5:1-8:1;

[0010] Component 1: by weight percentage, phenolic epoxy resin 24-35%, epoxy resin 9-20%, dispersant 0.4-2%, organic bentonite 0.3-0.7%, ion exchange corrosion inhibitor 3-9%, silicon micropowder 22-34%, oxide ceramic powder 5-13%, high-quality thin-layer graphene dispersion slurry 0.5-1.5%, carbon black 1.5-3%, defoamer 0.2-0.9%, xylene 3.0-5%, butanol 1.5-3%, acetone 2-5%, the sum of the weight percentages of the raw materials in component 1 is 100%;

[0011] Component 2: by weight percentage, 70-90% of modified alicyclic amine curing agent, 10-30% of modified fatty amine curing agent, and the sum of the weight percentages of the raw materials of component 2 is 100%.

[0012] Furthermore, the phenolic epoxy resin is Nan Ya 631, the epoxy resin is Nan Ya 128, the dispersant is BYD 2055, the organic bentonite is BYD 1958, the ion exchange corrosion inhibitor is Shuangma SM30, the silicon micropowder is Chuzhou Ge Rui Mining GA-1, the oxide ceramic powder is Shanghai Huijin Asia 3000 mesh, the high-quality thin layer graphene dispersion slurry is Grefeng GRF-FLG0D-04, the carbon black is Wuhai C611, the defoaming agent is BYD 1765, and xylene, butanol and acetone are all industrial grade commercial products.

[0013] Furthermore, the epoxy resin modified alicyclic amine curing agent adopts Jiadida 483M1, and the modified fatty amine curing agent adopts Jiadida 5473.

[0014] On the other hand, the present invention provides a production process for the above-mentioned ultra-high solid high temperature and high pressure resistant phenolic epoxy heavy anti-corrosion coating, comprising the following steps:

[0015] A: At a speed of 500 rpm, add phenolic epoxy resin, epoxy resin, and defoaming agent organic bentonite into a clean stirring kettle in sequence and stir evenly;

[0016] B: Increase the speed to 600 rpm, and continue to add dispersant, carbon black, high-quality thin-layer graphene dispersion slurry, oxide ceramic powder, ion exchange corrosion inhibitor, and silicon powder into the clean stirring kettle in sequence, and stir evenly;

[0017] C: Increase the speed to 1200 rpm, disperse at high speed for 30 minutes, and test the fineness of the obtained paint slurry;

[0018] D: After the fineness is qualified, reduce the speed to 800 rpm, add acetone, butanol and xylene, stir for 10-20 minutes until uniform, test the viscosity, specific gravity and sag, and filter with a filter basket after meeting the requirements of the central control index to obtain component 1 and package;

[0019] E: At a speed of 500 rpm, add modified alicyclic amine curing agent and modified fatty amine curing agent to a clean stirring kettle in sequence, increase the speed to 800 rpm, stir for 10-20 minutes until uniform, test the fineness of the obtained curing agent mixture, and after the fineness is qualified, test the viscosity, solid content and specific gravity. After meeting the requirements of the central control indicators, filter through silk to obtain component two and package it.

[0020] Furthermore, in step C, the slurry temperature is maintained at ≤50°C during high-speed dispersion.

[0021] Further, in step D, when the fineness is qualified, the paint slurry fineness is ≤40μm, the viscosity is, and the mesh number of the filter basket is 40 meshes.

[0022] Furthermore, in step E, when the fineness is qualified, the fineness of the curing agent mixture is ≤20 μm.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The ultra-high solid high temperature and high pressure resistant phenolic epoxy heavy anti-corrosion coating of the present invention has excellent acid resistance and heat resistance. The ion exchange corrosion inhibitor used is amorphous silica gel containing calcium ions, which improves the coating's resistance to carbon dioxide gas corrosion. When the corrosive electrolyte enters the coating film, that is, it comes into contact with the corrosion inhibitor, the corrosion inhibitor converts the acidic corrosive H +The calcium ions are intercepted on the surface of silica, releasing the corresponding calcium ions and transferring to the metal substrate, then the calcium ion layer accumulates on the metal / coating interface, thereby acting as a barrier to protect the substrate and enhancing the adhesion of the coating. Ceramic micropowder is a very good thermally stable material, which improves the heat resistance of the paint film. At the same time, ceramic micropowder contains a small amount of magnesium, titanium, and iron ions, which effectively promote the formation of a calcium ion shielding layer. The two work synergistically to form a dense protective layer, which enhances the coating's heat resistance and carbon dioxide corrosion resistance.

[0025] (2) The ultra-high solid high temperature and high pressure resistant phenolic epoxy heavy anti-corrosion coating of the present invention has excellent long-term anti-corrosion performance and wear resistance. The high-quality thin layer graphene dispersion slurry used maintains the crystallization quality of the original graphite flakes, the intact intra-layer sp2 structure and the electrical and thermal conductivity. The honeycomb crystal structure formed by the close arrangement of sp2 hybridized carbon atoms forms a van der Waals force with the calcium ions in the ion exchange corrosion inhibitor, thereby enhancing the density of the paint film and improving the anti-corrosion performance; at the same time, this chemical bond complex structure is more stable, which effectively enhances the wear resistance of the paint film, making the wear resistance of the paint film less than 12 mg.

[0026] (3) The ultra-high solid high temperature and high pressure resistant phenolic epoxy heavy-duty anti-corrosion coating of the present invention has excellent high temperature and high pressure resistance. The curing agent adopts modified alicyclic amine curing agent and modified fatty amine curing agent, both of which are multi-functional curing agents, so that the paint film has a high glass transition temperature and good chemical resistance, thereby giving the paint film excellent high temperature and high pressure resistance.

[0027] (4) The ultra-high solid, high temperature and high pressure resistant phenolic epoxy heavy-duty anti-corrosion coating of the present invention is a high solid content environmentally friendly product. The non-volatile matter of the coating in the construction state is greater than 90%, and the VOC content is less than 150g / L. When sprayed on the inner wall of a small-diameter pipe, a coating thickness of more than 200μm can be achieved in one time. It is safe, environmentally friendly, and has high construction efficiency.

[0028] (5) The inventors found in their research that there is a synergistic effect between the ion exchange corrosion inhibitor, the oxide ceramic powder, and the high-quality thin-layer graphene dispersion slurry. The three interact with each other to synergistically enhance the density of the paint film, thereby improving the overall performance of the paint film, especially the wear resistance. The adhesion is stable, making it more suitable for oil pipeline applications. When sprayed on the inner wall of the pipeline, the coating layer is firmly adhered to the surface of the metal pipeline, effectively preventing the metal from chemically reacting with external substances, thereby extending the service life of the pipeline and saving costs.

[0029] (6) The production process of the ultra-high solid high temperature and high pressure resistant phenolic epoxy heavy anti-corrosion coating of the present invention is simple, and is basically the same as the process operation of conventional solvent-based products, which can significantly improve production efficiency and reduce energy loss. The product quality solid content is above 90%, the film thickness is high after one construction, and the VOC content is low, which reduces the harm to construction personnel and the environment. In addition, the coating film has excellent corrosion resistance and high temperature and high pressure resistance, which can significantly improve the anti-corrosion life of the oil production pipeline, thereby increasing the oil production of the oil well and improving the utilization efficiency of the oil well. At the same time, acetone solvent with low boiling point and good solubility is added to the formula. When constructed in low temperature and narrow environment, it can evaporate quickly to form an excellent paint film appearance, thereby improving the pipeline coating efficiency. DETAILED DESCRIPTION

[0030] The technical solution of the present invention will be described clearly and completely in conjunction with the embodiments below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Example 1

[0032] The ultra-high solid high temperature and high pressure resistant phenolic epoxy heavy anti-corrosion coating of this embodiment is prepared by mixing component one and component two in a mass ratio of 6.5:1; wherein, component one is prepared with raw materials according to the following mass percentages: phenolic epoxy resin 24%, epoxy resin 20%, dispersant 0.4%, organic bentonite 0.7%, ion exchange corrosion inhibitor 3%, silicon micropowder 34%, oxide ceramic powder 5%, high-quality thin layer graphene dispersion slurry 0.5%, carbon black 1.5%, defoamer 0.9%, xylene 5%, butanol 3%, acetone 2%; component two is prepared with raw materials according to the following mass percentages: modified alicyclic amine curing agent 483M190%, modified fatty amine curing agent 547310%.

[0033] The phenolic epoxy resin in this embodiment is Nan Ya 631, the epoxy resin is Nan Ya 128, the dispersant is BYD 2055, the organic bentonite is BYD 1958, the ion exchange corrosion inhibitor is Shuangma SM30, the silicon micropowder is Chuzhou Ge Rui Mining GA-1, the oxide ceramic powder is Shanghai Huijin Asia 3000 mesh, the high-quality thin layer graphene dispersion slurry is Grefeng GRF-FLG0D-04, the carbon black is Wuhai C611, the defoaming agent is BYD 1765, and xylene, butanol and acetone are all industrial grade commercial products.

[0034] The preparation method of component one is as follows:

[0035] A: At a speed of 500 rpm, add phenolic epoxy resin, epoxy resin, and defoaming agent organic bentonite into a clean stirring kettle in sequence and stir evenly;

[0036] B: Increase the speed to 600 rpm, and continue to add dispersant, carbon black, high-quality thin-layer graphene dispersion slurry, oxide ceramic powder, ion exchange corrosion inhibitor, and silicon powder into the clean stirring kettle in sequence, and stir evenly;

[0037] C: Increase the speed to 1200 rpm, disperse at high speed for 30 minutes, and test the fineness of the obtained paint slurry to be ≤40μm;

[0038] D: After the fineness is qualified, reduce the speed to 800 rpm, add acetone, butanol and xylene, stir for 10-20 minutes until uniform, test the viscosity 100-116KU, and test the specific gravity and sag. After meeting the requirements of the central control index, filter with a 40-mesh copper mesh filter to obtain component one and package it.

[0039] The preparation method of component 2 is as follows:

[0040] At a speed of 500 rpm, add modified alicyclic amine curing agent and modified fatty amine curing agent to a clean stirring kettle in turn, increase the speed to 800 rpm, stir for 10-20 minutes until uniform, and test the fineness of the obtained curing agent mixture to 15μm. After the fineness is qualified, test the viscosity, solid content, and specific gravity. After meeting the requirements of the central control index, filter with silk to obtain component 2 and package.

[0041] After component one and component two are mixed according to the ratio, the ultra-high solid high temperature and high pressure resistant phenolic epoxy heavy anti-corrosion coating of this embodiment is formed, and a performance board is prepared by spraying. The performance test results are shown in Tables 1 and 2.

[0042] Example 2

[0043] The ultra-high solid high temperature and high pressure resistant phenolic epoxy heavy anti-corrosion coating of the present embodiment is formed by mixing component one and component two in a mass ratio of 7:1; wherein, component one is prepared with raw materials according to the following mass percentages: 35% phenolic epoxy resin, 9% epoxy resin, 1% dispersant, 0.3% organic bentonite, 9% ion exchange corrosion inhibitor, 25% silicon micropowder, 7% oxide ceramic powder, 1% high-quality thin layer graphene dispersion slurry, 3% carbon black, 0.2% defoamer, 3% xylene, 1.5% butanol, 5% acetone; component two is prepared with raw materials according to the following mass percentages: 170% modified alicyclic amine curing agent 483M and 30% modified fatty amine curing agent 5473.

[0044] The phenolic epoxy resin in this embodiment is Nan Ya 631, the epoxy resin is Nan Ya 128, the dispersant is BYD 2055, the organic bentonite is BYD 1958, the ion exchange corrosion inhibitor is Shuangma SM30, the silicon micropowder is Chuzhou Ge Rui Mining GA-1, the oxide ceramic powder is Shanghai Huijin Asia 3000 mesh, the high-quality thin layer graphene dispersion slurry is Grefeng GRF-FLG0D-04, the carbon black is Wuhai C611, the defoaming agent is BYD 1765, and xylene, butanol and acetone are all industrial grade commercial products.

[0045] The preparation method of component one is as follows:

[0046] A: At a speed of 500 rpm, add phenolic epoxy resin, epoxy resin, and defoaming agent organic bentonite into a clean stirring kettle in sequence and stir evenly;

[0047] B: Increase the speed to 600 rpm, and continue to add dispersant, carbon black, high-quality thin-layer graphene dispersion slurry, oxide ceramic powder, ion exchange corrosion inhibitor, and silicon powder into the clean stirring kettle in sequence, and stir evenly;

[0048] C: Increase the speed to 1200 rpm, disperse at high speed for 30 minutes, and test the fineness of the obtained paint slurry to be ≤40μm;

[0049] D: After the fineness is qualified, reduce the speed to 800 rpm, add acetone, butanol and xylene, stir for 10-20 minutes until uniform, test the viscosity 100-116KU, and test the specific gravity and sag. After meeting the requirements of the central control index, filter with a 40-mesh copper mesh filter to obtain component one and package it.

[0050] The preparation method of component 2 is as follows:

[0051] At a speed of 500 rpm, add modified alicyclic amine curing agent and modified fatty amine curing agent to a clean stirring kettle in turn, increase the speed to 800 rpm, stir for 10-20 minutes until uniform, and detect the fineness of the obtained curing agent mixture to be 15μm. After the fineness is qualified, test the viscosity, solid content and specific gravity. After meeting the requirements of the central control indicators, filter through silk to obtain component two and package it.

[0052] After component one and component two are mixed according to the ratio, the ultra-high solid high temperature and high pressure resistant phenolic epoxy heavy anti-corrosion coating of this embodiment is formed, and a performance board is prepared by spraying. The performance test results are shown in Tables 1 and 2.

[0053] Example 3

[0054] The ultra-high solid high temperature and high pressure resistant phenolic epoxy heavy anti-corrosion coating of the present embodiment is prepared by mixing component one and component two in a mass ratio of 8:1; wherein, component one is prepared with raw materials according to the following mass percentages: 30% phenolic epoxy resin, 11% epoxy resin, 2% dispersant, 0.5% organic bentonite, 8% ion exchange corrosion inhibitor, 22% silicon micropowder, 13% oxide ceramic powder, 1.5% high-quality thin layer graphene dispersion slurry, 2% carbon black, 0.5% defoamer, 3.5% xylene, 2.2% butanol, and 3.8% acetone; component two is prepared with raw materials according to the following mass percentages: 180% modified alicyclic amine curing agent 483M and 20% modified fatty amine curing agent 5473.

[0055] The phenolic epoxy resin in this embodiment is Nan Ya 631, the epoxy resin is Nan Ya 128, the dispersant is BYD 2055, the organic bentonite is BYD 1958, the ion exchange corrosion inhibitor is Shuangma SM30, the silicon micropowder is Chuzhou Ge Rui Mining GA-1, the oxide ceramic powder is Shanghai Huijin Asia 3000 mesh, the high-quality thin layer graphene dispersion slurry is Grefeng GRF-FLG0D-04, the carbon black is Wuhai C611, the defoaming agent is BYD 1765, and xylene, butanol and acetone are all industrial grade commercial products.

[0056] The preparation method of component one is as follows:

[0057] A: At a speed of 500 rpm, add phenolic epoxy resin, epoxy resin, and defoaming agent organic bentonite into a clean stirring kettle in sequence and stir evenly;

[0058] B: Increase the speed to 600 rpm, and continue to add dispersant, carbon black, high-quality thin-layer graphene dispersion slurry, oxide ceramic powder, ion exchange corrosion inhibitor, and silicon powder into the clean stirring kettle in sequence, and stir evenly;

[0059] C: Increase the speed to 1200 rpm, disperse at high speed for 30 minutes, and test the fineness of the obtained paint slurry to be ≤40μm;

[0060] D: After the fineness is qualified, reduce the speed to 800 rpm, add acetone, butanol and xylene, stir for 10-20 minutes until uniform, test the viscosity 100-116KU, and test the specific gravity and sag. After meeting the requirements of the central control index, filter with a 40-mesh copper mesh filter to obtain component one and package it.

[0061] The preparation method of component 2 is as follows:

[0062] At a speed of 500 rpm, add modified alicyclic amine curing agent and modified fatty amine curing agent to a clean stirring kettle in turn, increase the speed to 800 rpm, stir for 10-20 minutes until uniform, and detect the fineness of the obtained curing agent mixture to be 15μm. After the fineness is qualified, test the viscosity, solid content and specific gravity. After meeting the requirements of the central control indicators, filter through silk to obtain component two and package it.

[0063] After component one and component two are mixed according to the ratio, the ultra-high solid high temperature and high pressure resistant phenolic epoxy heavy anti-corrosion coating of this embodiment is formed, and a performance board is prepared by spraying. The performance test results are shown in Tables 1 and 2.

[0064] Table 1 Product coating performance test of Examples 1-3

[0065]

[0066]

[0067] The main technical indicators in Table 1 are tested in accordance with the requirements of the Petroleum and Natural Gas Industry Standard SY / T6717-2016 "Technical Conditions for Internal Coatings of Oil Pipes and Casings" of the People's Republic of China.

[0068] In order to examine whether the ultra-high solid high temperature and high pressure phenolic epoxy heavy anti-corrosion coatings of Examples 1-3 meet the actual anti-corrosion operation performance requirements of oil production pipelines, mechanical performance indicators such as impact resistance, hardness, bending resistance, pull-out adhesion and wear resistance were added on the basis of the above standard requirements. The test results are shown in Table 2.

[0069] Table 2 Mechanical properties test of products of Examples 1-3

[0070]

[0071] Comparative Example 1

[0072] The phenolic epoxy anti-corrosion coating of this comparative example is prepared by mixing component one and component two in a mass ratio of 8:1; wherein, component one is prepared with raw materials according to the following mass percentages: 30% phenolic epoxy resin, 11% epoxy resin, 2% dispersant, 0.5% organic bentonite, 30% silica powder, 13% oxide ceramic powder, 1.5% high-quality thin-layer graphene dispersion slurry, 2% carbon black, 0.5% defoamer, 3.5% xylene, 2.2% butanol, and 3.8% acetone; component two is prepared with raw materials according to the following mass percentages: 180% modified alicyclic amine curing agent 483M and 20% modified fatty amine curing agent 5473.

[0073] The phenolic epoxy resin in this comparative example is Nan Ya 631, the epoxy resin is Nan Ya 128, the dispersant is BYD 2055, the organic bentonite is BYD 1958, the silica micropowder is Chuzhou Ge Rui Mining GA-1, the oxide ceramic powder is Shanghai Huijin Asia 3000 mesh, the high-quality thin layer graphene dispersion slurry is Grefeng GRF-FLG0D-04, the carbon black is Wuhai C611, the defoaming agent is BYD 1765, and xylene, butanol and acetone are all industrial grade commercial products.

[0074] The preparation method of component one is as follows:

[0075] A: At a speed of 500 rpm, add phenolic epoxy resin, epoxy resin, and defoaming agent organic bentonite into a clean stirring kettle in sequence and stir evenly;

[0076] B: Increase the speed to 600 rpm, and continue to add dispersant, carbon black, high-quality thin-layer graphene dispersion slurry, oxide ceramic powder, ion exchange corrosion inhibitor, and silicon powder into the clean stirring kettle in sequence, and stir evenly;

[0077] C: Increase the speed to 1200 rpm, disperse at high speed for 30 minutes, and test the fineness of the obtained paint slurry to be ≤40μm;

[0078] D: After the fineness is qualified, reduce the speed to 800 rpm, add acetone, butanol and xylene, stir for 10-20 minutes until uniform, test the viscosity 100-116KU, and test the specific gravity and sag. After meeting the requirements of the central control index, filter with a 40-mesh copper mesh filter to obtain component one and package it.

[0079] The preparation method of component 2 is as follows:

[0080] At a speed of 500 rpm, add modified alicyclic amine curing agent and modified fatty amine curing agent to a clean stirring kettle in turn, increase the speed to 800 rpm, stir for 10-20 minutes until uniform, and detect the fineness of the obtained curing agent mixture to be 15μm. After the fineness is qualified, test the viscosity, solid content and specific gravity. After meeting the requirements of the central control indicators, filter through silk to obtain component two and package it.

[0081] After mixing component one and component two according to the proportion, the phenolic epoxy anticorrosive coating of this comparative example was formed, and a performance board was prepared by spraying. The performance test results are shown in Tables 3 and 4.

[0082] Comparative Example 2

[0083] The phenolic epoxy anti-corrosion coating of this comparative example is prepared by mixing component one and component two in a mass ratio of 8:1; wherein, component one is prepared with raw materials according to the following mass percentages: 30% phenolic epoxy resin, 11% epoxy resin, 2% dispersant, 0.5% organic bentonite, 34% silica powder, 9% ion exchange corrosion inhibitor, 1.5% high-quality thin layer graphene dispersion slurry, 2% carbon black, 0.5% defoamer, 3.5% xylene, 2.2% butanol, and 3.8% acetone; component two is prepared with raw materials according to the following mass percentages: 180% modified alicyclic amine curing agent 483M and 20% modified fatty amine curing agent 5473.

[0084] In this comparative example, the phenolic epoxy resin is Nan Ya 631, the epoxy resin is Nan Ya 128, the dispersant is BYK 2055, the organic bentonite is BYK 1958, the ion exchange corrosion inhibitor is Shuangma SM30, the silicon micropowder is Chuzhou Ge Rui Mining GA-1, the high-quality thin layer graphene dispersion slurry is Grefeng GRF-FLG0D-04, the carbon black is Wuhai C611, the defoaming agent is BYK 1765, and xylene, butanol and acetone are all industrial grade commercial products.

[0085] The preparation method of component one is as follows:

[0086] A: At a speed of 500 rpm, add phenolic epoxy resin, epoxy resin, and defoaming agent organic bentonite into a clean stirring kettle in sequence and stir evenly;

[0087] B: Increase the speed to 600 rpm, and continue to add dispersant, carbon black, high-quality thin-layer graphene dispersion slurry, oxide ceramic powder, ion exchange corrosion inhibitor, and silicon powder into the clean stirring kettle in sequence, and stir evenly;

[0088] C: Increase the speed to 1200 rpm, disperse at high speed for 30 minutes, and test the fineness of the obtained paint slurry to be ≤40μm;

[0089] D: After the fineness is qualified, reduce the speed to 800 rpm, add acetone, butanol and xylene, stir for 10-20 minutes until uniform, test the viscosity 100-116KU, and test the specific gravity and sag. After meeting the requirements of the central control index, filter with a 40-mesh copper mesh filter to obtain component one and package it.

[0090] The preparation method of component 2 is as follows:

[0091] At a speed of 500 rpm, add modified alicyclic amine curing agent and modified fatty amine curing agent to a clean stirring kettle in turn, increase the speed to 800 rpm, stir for 10-20 minutes until uniform, and detect the fineness of the obtained curing agent mixture to be 15μm. After the fineness is qualified, test the viscosity, solid content and specific gravity. After meeting the requirements of the central control indicators, filter through silk to obtain component two and package it.

[0092] After mixing component one and component two according to the proportion, the phenolic epoxy anticorrosive coating of this comparative example was formed, and a performance board was prepared by spraying. The performance test results are shown in Tables 3 and 4.

[0093] Comparative Example 3

[0094] The phenolic epoxy anti-corrosion coating of this comparative example is prepared by mixing component one and component two in a mass ratio of 8:1; wherein, component one is prepared with raw materials according to the following mass percentages: 30% phenolic epoxy resin, 11% epoxy resin, 2% dispersant, 0.5% organic bentonite, 29.5% silica powder, 5% ion exchange corrosion inhibitor, 10% oxide ceramic powder, 2% carbon black, 0.5% defoamer, 3.5% xylene, 2.2% butanol, and 3.8% acetone; component two is prepared with raw materials according to the following mass percentages: 180% modified alicyclic amine curing agent 483M and 20% modified fatty amine curing agent 5473.

[0095] In this comparative example, the phenolic epoxy resin is Nan Ya 631, the epoxy resin is Nan Ya 128, the dispersant is BYK 2055, the organic bentonite is BYK 1958, the ion exchange corrosion inhibitor is Shuangma SM30, the silica micropowder is Chuzhou Ge Rui Mining GA-1, the oxide ceramic powder is Shanghai Huijin Ya 3000 mesh, the carbon black is Wuhai C611, the defoaming agent is BYK 1765, and xylene, butanol and acetone are all industrial grade commercial products.

[0096] The preparation method of component one is as follows:

[0097] A: At a speed of 500 rpm, add phenolic epoxy resin, epoxy resin, and defoaming agent organic bentonite into a clean stirring kettle in sequence and stir evenly;

[0098] B: Increase the speed to 600 rpm, and continue to add dispersant, carbon black, high-quality thin-layer graphene dispersion slurry, oxide ceramic powder, ion exchange corrosion inhibitor, and silicon powder into the clean stirring kettle in sequence, and stir evenly;

[0099] C: Increase the speed to 1200 rpm, disperse at high speed for 30 minutes, and test the fineness of the obtained paint slurry to be ≤40μm;

[0100] D: After the fineness is qualified, reduce the speed to 800 rpm, add acetone, butanol and xylene, stir for 10-20 minutes until uniform, test the viscosity 100-116KU, and test the specific gravity and sag. After meeting the requirements of the central control index, filter with a 40-mesh copper mesh filter to obtain component one and package it.

[0101] The preparation method of component 2 is as follows:

[0102] At a speed of 500 rpm, add modified alicyclic amine curing agent and modified fatty amine curing agent to a clean stirring kettle in turn, increase the speed to 800 rpm, stir for 10-20 minutes until uniform, and detect the fineness of the obtained curing agent mixture to be 15μm. After the fineness is qualified, test the viscosity, solid content and specific gravity. After meeting the requirements of the central control indicators, filter through silk to obtain component two and package it.

[0103] After mixing component one and component two according to the proportion, the phenolic epoxy anticorrosive coating of this comparative example was formed, and a performance board was prepared by spraying. The performance test results are shown in Tables 3 and 4.

[0104] Table 3 Coating performance test results of the products of Comparative Examples 1-3

[0105]

[0106] The main technical indicators in Table 3 are tested in accordance with the requirements of the Petroleum and Natural Gas Industry Standard SY / T6717-2016 "Technical Conditions for Internal Coatings of Oil Pipes and Casings" of the People's Republic of China.

[0107] In order to verify the synergistic effect among ion exchange corrosion inhibitor, oxide ceramic powder and high-quality thin-layer graphene dispersion slurry, mechanical performance indicators such as impact resistance, hardness, bending resistance, pull-out adhesion and wear resistance were added on the basis of the above standard requirements. The test results are shown in Table 4.

[0108] Table 4 Mechanical properties test of products of comparative examples 1-3

[0109]

[0110] The test results in Table 1-2 show that the coating formed by the ultra-high solid high temperature and high pressure resistant phenolic epoxy heavy anti-corrosion coating of the present invention has a flat, uniform and smooth appearance, without blistering, orange peel and flowing phenomena, high adhesion, and excellent corrosion resistance, wear resistance, high temperature and high pressure resistance, and can meet the actual anti-corrosion operation performance requirements of oil production pipelines.

[0111] The test results in Tables 1-4 show that the pull-out adhesion of the ultra-high solid, high temperature and high pressure resistant phenolic epoxy heavy anti-corrosion coatings of Examples 1-3 are all 18MPa, and the wear resistance is not higher than 12mg, while the pull-out adhesion of the phenolic epoxy anti-corrosion coatings of Comparative Examples 1-3 are 13MPa, 16MPa, and 11MPa, respectively, and are all lower than 18MPa, and the wear resistance is greater than 25mg; it can be seen that the ultra-high solid, high temperature and high pressure resistant phenolic epoxy heavy anti-corrosion coatings of Examples 1-3 have stable pull-out adhesion and the wear resistance is improved by at least twice. The test results in Tables 1-4 verify that there is a synergistic effect between the ion exchange corrosion inhibitor, oxide ceramic powder, and high-quality thin-layer graphene dispersion slurry. The three interact with each other to synergistically enhance the density of the paint film, thereby improving the overall performance of the paint film, especially the wear resistance. The adhesion is stable and it is more suitable for oil pipeline application scenarios. When sprayed on the inner wall of the pipeline, the coating layer is firmly adhered to the surface of the metal pipeline, which effectively prevents chemical reactions between the metal and external substances, prolongs the service life of the pipeline, saves costs, and can significantly enhance the density of the paint film, so that the paint film has excellent long-term anti-corrosion and wear resistance.

Claims

1. Ultra-high solid high temperature and high pressure resistant phenolic epoxy heavy anti-corrosion coating, characterized by: It is prepared by mixing component one and component two in a mass ratio of 6.5:1-8:1; Component 1: by weight percentage, phenolic epoxy resin 24-35%, epoxy resin 9-20%, dispersant 0.4-2%, organic bentonite 0.3-0.7%, ion exchange corrosion inhibitor 3-9%, silicon micropowder 22-34%, oxide ceramic powder 5-13%, high-quality thin-layer graphene dispersion slurry 0.5-1.5%, carbon black 1.5-3%, defoamer 0.2-0.9%, xylene 3.0-5%, butanol 1.5-3%, acetone 2-5%, the sum of the weight percentages of the raw materials in component 1 is 100%; Component 2: by weight percentage, modified alicyclic amine curing agent 70-90%, modified fatty amine curing agent 10-30%, and the sum of the weight percentages of the raw materials of component 2 is 100%.

2. The ultra-high solid high temperature and high pressure resistant phenolic epoxy heavy anti-corrosion coating according to claim 1, characterized in that: The phenolic epoxy resin is Nan Ya 631, the epoxy resin is Nan Ya 128, the dispersant is BYD 2055, the organic bentonite is BYD 1958, the ion exchange corrosion inhibitor is Shuangma SM30, the silicon micropowder is Chuzhou Ge Rui Mining GA-1, the oxide ceramic powder is Shanghai Huijin Asia 3000 mesh, the high-quality thin layer graphene dispersion slurry is Grefeng GRF-FLG0D-04, the carbon black is Wuhai C611, the defoaming agent is BYD 1765, and xylene, butanol and acetone are all industrial grade commercial products.

3. The ultra-high solid high temperature and high pressure resistant phenolic epoxy heavy anti-corrosion coating according to claim 1, characterized in that: The epoxy resin modified alicyclic amine curing agent adopts Jiadida 483M1, and the modified fatty amine curing agent adopts Jiadida 5473.

4. The production process of the ultra-high solid high temperature and high pressure resistant phenolic epoxy heavy anticorrosive coating according to any one of claims 1 to 3, characterized in that: The following steps are involved: A: At a speed of 500 rpm, add phenolic epoxy resin, epoxy resin, and defoaming agent organic bentonite into a clean stirring kettle in sequence and stir evenly; B: Increase the speed to 600 rpm, and continue to add dispersant, carbon black, high-quality thin-layer graphene dispersion slurry, oxide ceramic powder, ion exchange corrosion inhibitor, and silicon powder into the clean stirring kettle in sequence, and stir evenly; C: Increase the speed to 1200 rpm, disperse at high speed for 30 minutes, and test the fineness of the obtained paint slurry; D: After the fineness is qualified, reduce the speed to 800 rpm, add acetone, butanol and xylene, stir for 10-20 minutes until uniform, test the viscosity, specific gravity and sag, and filter with a filter basket after meeting the requirements of the central control index to obtain component 1 and package; E: At a speed of 500 rpm, add modified alicyclic amine curing agent and modified fatty amine curing agent to a clean stirring kettle in sequence, increase the speed to 800 rpm, stir for 10-20 minutes until uniform, test the fineness of the obtained curing agent mixture, and after the fineness is qualified, test the viscosity, solid content and specific gravity. After meeting the requirements of the central control indicators, filter through silk to obtain component two and package it.

5. The production process according to claim 4, characterized in that: In step C, the paint slurry temperature is maintained at ≤50°C during high-speed dispersion.

6. The production process according to claim 4, characterized in that: In step D, when the fineness is qualified, the paint slurry fineness is ≤40μm, the viscosity is, and the mesh number of the filter basket is 40 meshes.

7. The production process according to claim 4, characterized in that: In step E, when the fineness is qualified, the fineness of the curing agent mixture is ≤20 μm.

Citation Information

Patent Citations

  • Heavy-duty paint

    CN108384397A

  • High-temperature-resistant and high-pressure-resistant graphene modified phenolic resin coating

    CN109401555A

  • High temperature and high pressure-resistant type graphene-modified phenolic heavy-duty anti-corrosive coating for oil pipe

    CN109517492A

  • Anticorrosive paint, preparation method and application thereof, and coated product

    CN118599391A

  • Corrosion resistant workpiece for nuclear power plant

    CN118600420A